Evaluation of outsourcing development in the service sector - Ugnė Dudė; Rima Žitkienė; Daiva Jurevičienė; Viktorija Skvarciany; Indre Lapinskaite (Economies, 2021)
The global pandemic has affected all sectors and disrupted not only supply chains but also had a particular impact on the range of services provided and the whole service sector. Outsourcing is used to adapt to business environment changes. However, in the scholarly literature, outsourcing of services is analysed as a complementary part of the manufacturing process - there is a lack of research on outsourcing in service companies. This article analyses the enablers of outsourcing in all service groups. The aim of the semi-structured interview was to determine not only the enablers, their significance in each WTO (World Trade Organisation) group of services but also the use of outsourcing in the provision of core and non-core services. The results of the empirical study revealed that outsourcing is increasingly used in the service sector; however, enablers vary depending on the provision of services, the nature of the service company's activities, and the needs they meet, public or for-profit.
Keywords: L80; O14; 330; outsourcing; outsourcing drivers; service companies